Geographical Text Analysis: A new approach to understanding nineteenth-century mortality. (November 2015) - Porter, Catherine; Atkinson, Paul; Gregory, Ian
Abstract: This paper uses a combination of Geographic Information Systems (GIS) and corpus linguistic analysis to extract and analyse disease related keywords from the Registrar-General's Decennial Supplements. Combined with known mortality figures, this provides, for the first time, a spatial picture of the relationship between the Registrar-General's discussion of disease and deaths in England and Wales in the nineteenth and early twentieth centuries. Techniques such as collocation, density analysis, the Hierarchical Regional Settlement matrix and regression analysis are employed to extract and analyse the data resulting in new insight into the relationship between the Registrar-General's published texts and the changing mortality patterns during this time. Highlights: We combine GIS and corpus linguistics in the form of Geographical Text Analysis. This allows comparison of the geography of a text with spatial distribution data. We examine health reports and mortality data in 19th century England and Wales. The disease mentions in the reports did not correlate with mortality statistics. Central authorities׳ approach was discursive rather than focussed on disease burdens.